2014
DOI: 10.1371/journal.pone.0105412
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Profiling of Polar Metabolites in Herbal Medicine Injections for Multivariate Statistical Evaluation Based on Independence Principal Component Analysis

Abstract: Botanical primary metabolites extensively exist in herbal medicine injections (HMIs), but often were ignored to control. With the limitation of bias towards hydrophilic substances, the primary metabolites with strong polarity, such as saccharides, amino acids and organic acids, are usually difficult to detect by the routinely applied reversed-phase chromatographic fingerprint technology. In this study, a proton nuclear magnetic resonance (1H NMR) profiling method was developed for efficient identification and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…DHI is one of the simplest and chemically best resolved CCM. We and others have introduced new techniques such as 1 H NMR to identify and quantify additional ingredients 62 , 64 . More advanced ingredient identification method, such as 2D LC/QTOF, should be applied to identify more ingredients in DHI, which will benefit our understanding of its therapeutic effects 101 .…”
Section: Discussionmentioning
confidence: 99%
“…DHI is one of the simplest and chemically best resolved CCM. We and others have introduced new techniques such as 1 H NMR to identify and quantify additional ingredients 62 , 64 . More advanced ingredient identification method, such as 2D LC/QTOF, should be applied to identify more ingredients in DHI, which will benefit our understanding of its therapeutic effects 101 .…”
Section: Discussionmentioning
confidence: 99%
“…[21, 22]. We have previously characterized the major constituents of DHI by ultra-performance liquid chromatography (UPLC) [23] and proton nuclear magnetic resonance ( 1 H NMR) [24]. Recently, other investigators have separated and identified further constituents in DHI by UPLC [22].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously identified 11 polyphenolic acids in DHI using ultra-performance liquid chromatography (UPLC) coupled with UV detection [8]. With a newly developed proton nuclear magnetic resonance (1H NMR) profiling method, we also simultaneously identified and quantified 23 primary metabolites together with 7 polyphenolic acids in DHI [9]. Recently, other investigators have further characterized and identified a total of 63 compounds, including 33 phenolic acids, 2 C-glycosyl quinochalcones, 6 flavonoid O-glycosides, 4 iridoid glycosides, 6 organic acids, 5 amino acids, and 3 nucleosides in DHI [10].…”
Section: Introductionmentioning
confidence: 99%